An Over-the-Counter Hearing Aid Clinical Trial in Rural Alabama: Project Design and Potential Implications for Pharmacy and Audiology Interprofessional Collaborations - Marcia J. Hay-McCutcheon; Abigail F. Hubbard; Emma B. Brothers; Rebecca S. Allen; Xin Yang (MDPI AG, 2024)
Over-the-counter hearing aids (OTC HAs) have the potential to help adults with perceived mild-to-moderate hearing loss across the US, especially in rural communities, where access to hearing healthcare is extremely limited or non-existent. The purpose of this study was to describe an OTC HA clinical trial being conducted in five rural counties of Alabama and to provide preliminary anecdotal data related to the use and care of these hearing aids by the participants. In brief, for this clinical trial, adults with hearing loss were randomly placed in one of three groups where they received varying levels of support for setting, using, and maintaining their OTC HAs. Listening tests and surveys were administered to assess the extent to which they benefitted from the hearing aids as related to word understanding, communication with others in natural settings, and hearing aid use and care. Currently, anecdotal findings suggested that, although some participants required very little support to successfully use their hearing aids, others had difficulty setting and caring for their devices and could have benefitted from individualized guidance. Future quantitative studies will assess the extent of support needed for successful hearing aid benefit and use. Potentially, collaborations among pharmacy and audiology professionals could lead to increased access to hearing healthcare by supporting the use and purchase of OTC HAs in rural pharmacy settings.